Theoretical and experimental evaluation of SEPIC‐based DC–DC converters with two‐winding and three‐winding coupled inductors. (26th June 2022) - Mahmoudi, Mohsen; Ajami, Ali; Babaei, Ebrahim; Soleimanifard, Javad
Abstract: In this paper, an SEPIC‐based direct current–direct current (DC–DC) converter with high voltage gain and continuous input current is provided. Input current Continuity is a great advantage for renewable resources applications, and a small filter can be used in the output of these sources. Also in this paper, the effect of coupled inductor in three‐winding structure is discussed compared to the two‐winding coupled inductor. Precise analysis of converters based on two‐winding and three‐winding coupling inductors requires that the structures be similar so that the evaluation can be performed correctly. A comparison is performed between the two‐winding coupled inductor‐based converter and the improved converter to show the advantages of the proposed converter. All elements of the converter have been compared, and since both converters are different in terms of coupled inductor, complete analyses have been done in the field of calculating inductors. In addition to the features of the two‐winding coupled inductor converter, the proposed converter requires smaller coupled inductor to decrease the core size and increase the converter efficiency. Abstract : An SEPIC‐based DC–DC converter with high voltage gain and continuous input current is provided. The effects of coupled inductor in three‐winding and two‐winding structures are discussed. In addition to advantages of two‐winding coupled inductor converter, the proposed converter requires smaller coupled inductor to decrease the core size and increase efficiency.